LUMINESCENCE OF ALUMINUM OXIDE FILMS AND PERSPECTIVES OF THEIR APPLICATION IN NANOPHOTONICS PLANAR MICROSTRUCTURES - L. S. Khoroshko; T. I. Orekhovskaya; M. V. Meledina; I. A. Nikolaenko; A. S. Kochev; A. M. Asharif; B. S. Kolosnitsyn; N. V. Gaponenko; A. V. Mudry (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Various methods of fabrication the luminescent film structures based on porous anodic alumina are analyzed. Manufacturing of luminescent structures by anodizing aluminum in oxalic acid allows observation of visible to the naked eye photoluminescence in the blue range, which remains under ambient conditions for a year or longer. Alumina xerogel prepared in a form of powder demonstrates luminescence in the blue range, which disappears totally after annealing at 800 ºC. Photoluminescence of porous anodic alumina which contains terbium ions in the xerogel of alumina or deposited from solutions of salts formed in the anodic alumina pores has been investigated. The perspectives of formation of planar microstructures using a porous anodic alumina supporting electromagnetic whispering gallery modes are discussed.